Sub-leading flow modes in PbPb collisions at from the HYDJET++ model *Supported by Ministry of Education, Science and Technological Development of the Republic of Serbia (171019). (July 2017) - Cirkovic, P.; Devetak, D.; Dordevic, M.; Milosevic, J.; Stojanovic, M.
Abstract: Recent LHC results on the appearance of sub-leading flow modes in PbPb collisions at 2.76 TeV, related to initial-state fluctuations, are analyzed and interpreted within the HYDJET++ model. Using the newly introduced Principal Component Analysis (PCA) method applied to two-particle azimuthal correlations extracted from the model calculations, the leading and sub-leading flow modes are studied as a function of the transverse momentum ( p T ) over a wide centrality range. The leading modes of the elliptic and triangular flow calculated with the HYDJET++ model reproduce rather well the v 2 {2} and v 3 {2} coefficients measured experimentally using the two-particle correlations. Within the p T ⩽ 3 GeV/ c range, where hydrodynamics dominates, the sub-leading flow effects are greatest at the highest p T of around 3 GeV/c. The sub-leading elliptic flow mode, which corresponds to the n = 2 harmonic, has a small non-zero value and slowly increases from central to peripheral collisions, while the sub-leading triangular flow mode, which corresponds to the n =3 harmonic, is even smaller and does not depend on centrality. For n = 2, the relative magnitude of the effect measured with respect to the leading flow mode shows a shallow minimum for semi-central collisions and increases for very central and for peripheral collisions. For the n = 3 case, there is no centrality dependence. The sub-leading flow mode results obtained from the HYDJET++ model are in rather good agreement with the experimental measurements of the CMS Collaboration.